Italian Guidelines for the Management of Sporadic Primary Hyperparathyroidism - Vescini, Fabio; Borretta, Giorgio; Chiodini, Iacopo; Boniardi, Marco; Carotti, Marina; Castellano, Elena; Cipriani, Cristiana; Eller-Vainicher, Cristina; Giannini, Sandro; Iacobone, Maurizio; Salcuni, Antonio Stefano; Saponaro, Federica; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Aim: This guideline (GL) is aimed at providing a clinical practice reference for the management of sporadic primary hyperparathyroidism (PHPT) in adults. PHPT management in pregnancy was not considered. Methods: This GL has been developed following the methods described in the Manual of the Italian National Guideline System. For each question, the panel appointed by Associazione Medici Endocrinology (AME) and Società Italiana dell’Osteoporosi, del Metabolismo Minerale e delle Malattie dello Scheletro (SIOMMMS) identified potentially relevant outcomes, which were then rated for their impact on therapeutic choices. Only outcomes classified as “critical” and “important” were considered in the systematic review of evidence. Those classified as “critical” were considered for the clinical practice recommendations. Results: The present GL provides recommendations about the roles of pharmacological and surgical treatment for the clinical management of sporadic PHPT. Parathyroidectomy is recommended in comparison to surveillance or pharmacologic treatment in any adult (outside of pregnancy) or elderly subject diagnosed with sporadic PHPT who is symptomatic or meets any of the following criteria: • Serum calcium levels >1 mg/dL above the upper limit of normal range. • Urinary calcium levels >4 mg/kg/day. • Osteoporosis disclosed by DXA examination and/or any fragility fracture. • Renal function impairment (eGFR <60 mL/min). • Clinic or silent nephrolithiasis. • Age ≤50 years. Monitoring and treatment of any comorbidity or complication of PHPT at bone, kidney, or cardiovascular level are suggested for patients who do not meet the criteria for surgery or are not operated on for any reason. Sixteen indications for good clinical practice are provided in addition to the recommendations. Conclusion: The present GL is directed to endocrinologists and surgeons - working in hospitals, territorial services or private practice - and to general practitioners and patients. The recommendations should also consider the patient’s preferences and the available resources and expertise.
Keywords: surveillance